Counseling on Family Health Tasks in Preventing Febrile Seizures in Children - Qasim, Muhammad; Juwita, Helmi (Bantayang Omni Cendekia, 2024)
Background: Febrile seizures are fevers that usually attack children aged 6 months to 5 years with a relatively high recurrence rate and are the most frightening experience for parents. In preventing febrile seizures in children, it is necessary to have counseling on family health tasks. Family tasks in the health sector are highly expected in the family environment with the hope of taking care of the family's health properly. Objective: This study aims to determine the effect of counseling family health tasks in preventing febrile seizures in children. Methods: This study uses a quasi-experimental design with a pre-post test design approach. The sampling technique used purposive sampling technique. The sample in this study amounted to 44 people. The research instrument used a research questionnaire based on Friedman's theory. Data analysis used the Mcnemar test. Results: respondents' knowledge increased after counseling on Family Health Tasks in Preventing Febrile Seizures in Children with the McNemar test result value with p = 0.001 when compared to the value of α = 0.05, then ρ <α. This shows that there is an influence of Counseling on Family Health Tasks in Preventing Febrile Seizures in Children. Conclusion: There is an influence of family health task counseling in preventing febrile seizures in children on family knowledge before and after counseling. Keywords: Counseling; Family Health Tasks; Febrile Seizures